2017
DOI: 10.1098/rsos.170185
|View full text |Cite
|
Sign up to set email alerts
|

Operating length and velocity of human M. vastus lateralis fascicles during vertical jumping

Abstract: Humans achieve greater jump height during a counter-movement jump (CMJ) than in a squat jump (SJ). However, the crucial difference is the mean mechanical power output during the propulsion phase, which could be determined by intrinsic neuro-muscular mechanisms for power production. We measured M. vastus lateralis (VL) fascicle length changes and activation patterns and assessed the force–length, force–velocity and power–velocity potentials during the jumps. Compared with the SJ, the VL fascicles operated on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 50 publications
6
54
0
Order By: Relevance
“…This is consistent with previous studies on the medial gastrocnemius muscle during walking, running, and bilateral jumping Lichtwark and Wilson, 2006;Farris and Sawicki, 2012;Aeles et al, 2018) and with results from other triceps surae muscles such as the lateral gastrocnemius and soleus (Cronin and Finni, 2013;Lai et al, 2015). In a recent study on the muscle-tendon interaction in the vastus lateralis muscle, also no active stretching of the muscle fascicles was found during a squat jump (Nikolaidou et al, 2017). In the study by Nikolaidou et al (2017), the fascicles did lengthen in the counter-movement jump, however, this occurs prior to activation of the muscle, as can be seen from the EMG data, and is therefore not considered an active SSC.…”
Section: Absence Of a Ssc In The Muscles Fasciclessupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous studies on the medial gastrocnemius muscle during walking, running, and bilateral jumping Lichtwark and Wilson, 2006;Farris and Sawicki, 2012;Aeles et al, 2018) and with results from other triceps surae muscles such as the lateral gastrocnemius and soleus (Cronin and Finni, 2013;Lai et al, 2015). In a recent study on the muscle-tendon interaction in the vastus lateralis muscle, also no active stretching of the muscle fascicles was found during a squat jump (Nikolaidou et al, 2017). In the study by Nikolaidou et al (2017), the fascicles did lengthen in the counter-movement jump, however, this occurs prior to activation of the muscle, as can be seen from the EMG data, and is therefore not considered an active SSC.…”
Section: Absence Of a Ssc In The Muscles Fasciclessupporting
confidence: 92%
“…In a recent study on the muscle-tendon interaction in the vastus lateralis muscle, also no active stretching of the muscle fascicles was found during a squat jump (Nikolaidou et al, 2017). In the study by Nikolaidou et al (2017), the fascicles did lengthen in the counter-movement jump, however, this occurs prior to activation of the muscle, as can be seen from the EMG data, and is therefore not considered an active SSC. In other studies that have shown stretching of the muscle fascicles in the medial gastrocnemius and soleus, vastus laterlias, and tibialis posterior, et al, 2017).…”
Section: Absence Of a Ssc In The Muscles Fasciclesmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, as shown in Figure 1, the main length changes of the VL MTU were primarily associated with changes of the series‐elastic elements of the VL (patellar and quadriceps tendon complex). This SEE behavior allows the fascicles to take advantage of the high force‐length‐velocity potentials during the active phase of the stance phase where the VL muscle generates force 23,38 …”
Section: Discussionmentioning
confidence: 99%
“…The images generated by this method are complex, and require a great deal of time and effort from practitioners to interpret and extract meaning from them. In recent years, efforts have been made to automate parts of this process [5][6][7][8][9][10]. However, these efforts have been fragmented, and suffer from a number of limitations: they often focus on analysing a single parameter of interest; most publications do not reveal specific details of how to implement the method; some methods rely on software that require expensive licence fees; the majority of methods are only semi-automated, requiring manual, subjective interpretation of at least some images; and often tracking methods involve complex mathematics and require computer programming experience.…”
Section: Introductionmentioning
confidence: 99%